In-situ reference data for aboveground vegetation traits of pre-Alpine grasslands in southern Germany - Anne Schucknecht; Alexander Krämer; Sarah Asam; Abraham Mejia Aguilar; Noelia Garcia Franco; Max A Schuchardt; Anke Jentsch; Ralf Kiese (PANGAEA, 2020)
The data package compiles vegetation data of ten temperate pre-Alpine managed grasslands in southern Germany. The first dataset originates from a sampling campaign in April 2018. A 30 m x 30 m homogenous flat plot was selected at each of the ten grasslands and sampled at nine to twelve 0.25 m x 0.25 m subplots. After determining the bulk canopy height of the subplot, the vegetation was cut at 0.03 m. Afterwards the following parameters of the cut vegetation were determined in the laboratory: weight of the fresh and dry biomass; weight percentage of the plant functional types (PFT) non-green vegetation, legumes, graminoids, other forbs; total green area index (GAI) and PFT-specific GAI; carbon (C) and nitrogen (N) content of the PFT. Water content and mean C and N contents were calculated from measured values. Additional samples around the subplots were taken to determine the leaf mass per area (LMA) of PFTs that occur in the plot. The second data set is based on a vegetation survey from June 2020 at exactly the same ten plots and includes grassland type, plant species richness and species coverage of the plots. The data package was obtained within the framework of the SUSALPS project (https://www.susalps.de/) to provide in-situ data for the estimation of grassland parameters with unmanned aircraft system (UAS)-based and satellite-based remote sensing data.